HADHANAH IN THE CONCEPT OF COMPILATION OF ISLAMIC LAW AND LAW - Firdausia, Salsabila (Nurani, 2020)
KHI states that hadanah for a child who is not mumayyiz or not yet 12 (twelve) years old is the right of his mother. The basis of the 12-year law is not found in the Al- Qur'an, hadits and fiqh literature. Therefore, the author conducts research to determine the hadanah in the concept of KHI and Undang-undang. This type of research is yuridis normatif. The source of this research data is secondary data. Based on the results of the study, the hadhanah rights remain with both parents even if the parents are divorced. It is mentioned in the KHI, UU Perkawinan and UU Perlindungan Anak that giving love to a child is an obligation attached to the parents towards the child from the time the child is in the womb until the end of his life.